Overcoming resistance to anti-PD1 and anti-PD-L1 treatment in gastrointestinal malignancies. Issue 1 (10th May 2020) - Puccini, Alberto; Battaglin, Francesca; Iaia, Maria Laura; Lenz, Heinz-Josef; Salem, Mohamed E
Abstract : In the last few years, the unprecedented results of immune checkpoint inhibitors have led to a paradigm shift in clinical practice for the treatment of several cancer types. However, the vast majority of patients with gastrointestinal cancer do not benefit from immunotherapy. To date, microsatellite instability high and DNA mismatch repair deficiency are the only robust predictive biomarkers of response to immune checkpoint inhibitors. Unfortunately, these patients comprise only 5%–10% of all gastrointestinal cancers. Several mechanisms of both innate and adaptive resistance to immunotherapy have been recognized that may be at least in part responsible for the failure of immune checkpoint inhibitors in this population of patients. In the first part of this review article, we provide an overview of the main clinical trials with immune checkpoint inhibitors in patients with gastrointestinal cancer and the role of predictive biomarkers. In the second part, we discuss the actual body of knowledge in terms of mechanisms of resistance to immunotherapy and the most promising approach that are currently under investigation in order to expand the population of patients with gastrointestinal cancer who could benefit from immune checkpoint inhibitors.